Rupiah currency strengthening at border area West Kalimantan Province - Gun Tembawang, Suruh Tembawang Village, Entikong District - Sri Haryaningsih, M.Si; Ira Patriani, M.Si (African Journal of Hospitality, Tourism and Leisure, 2019)
The use of Malaysian Ringgit in Dusun Gun Tembawang, Suruh Tembawang Village, Entikong District, Sanggau Regency, West Kalimantan Province is very low and there are almost no transactions on Rupiah in this area including tourists use. This study used qualitative research methods with data collection namely observation techniques, conducted by researchers directly observing the actions and activities in the field related to the focus of problems and interview techniques, conducted by researchers by making a series of question lists which contains the main issues that will be asked to the informant or subject related to get the information or data needed. Based on the results of research Gun Tembawang community do not recognize the Rupiah currency and in each transaction they use the Malaysian Ringgit currency and in their daily needs the community is still dependent on the State Neighbours namely Malaysia. The implementation of Bank Indonesia Regulation Number 17/3/2015, Regarding the Obligation to Use the Rupiah in Gun Tembawang has not been optimal. Policy objectives must be clear and measurable so that they can be realized, for example policy objectives, policy directions and policy objectives that have an impact on economic conditions, and social conditions . The District Government and the Central Government immediately need to complete the road infrastructure at the border that can connect Gun Tembawang to the village center, and the regional government center, because the main factors which are most influential to change things as they are now, are road infrastructure development and education.